The impact of geographic reputation on the value created in Champagne. (8th November 2013) - Menival, David; Charters, Steve
<x xml:space="preserve">Abstract</x> With asymmetric information, consumers need to rely on the reputation of wine to define quality before the purchasing. Amongst the tools available for underlining reputation, geographic location is considered to offer high potential. Today, some wines benefit from a country's reputation, some from the renown of a region and some from the local reputation of one specific vineyard, whilst conversely some providers suffer from a weak geographic reputation. There can be a split between producers within one vineyard or region based on varying geographic reputation. This kind of split appears in Champagne, with a range of well‐known and less well‐known brands and is particularly significant to the small growers who sell wine. This study used a representative sample of these growers to examine how their location impacts on their reputation. The results show that their selling price is influenced by the local system of grading vineyard quality, their distance from traditional regional centres and the presence in their village of growers cited in a national guide.